Impact of Macro-Economic Factors on the International Tourist Arrivals: An Analysis of Sri Lanka and its Regional Competitors - Assella, A.P.N.; Pathirana, A.P.R.P.; Wijekoon, H.M.S.D. (NSBM Green University, 2022)
Globally, tourism has become one of the most rapidly expanding industries because of its economic and cultural importance. Understanding how dynamic economic conditions affect tourism development in Sri Lanka is crucial in achieving the future development goals of the country. This paper investigates the impact of the Gross Domestic Product (GDP), Foreign Direct Investment (FDI), and Inflation Rate (IR) on International Tourist Arrivals (ITA) of Sri Lanka and its two regional competitors, i.e., Malaysia andSingapore. Annual data of variables were extracted from the World Banks Database for the period of 1995 to 2019. The Descriptive analysis was carried out to compare the behavior of the different variables among the selected countries. The effect of macroeconomic variables on tourist arrivals in each country was examined by employing multiple linear regression analysis. It was identified that GDP contributes positively to tourism visits in each country. Further, inSingapore, FDI positively impacts tourist arrivals, whereas Sri Lanka and Malaysia haven't experienced any significant changes due to FDI.However, fluctuations in tourist arrivals in any country did not correlate with changes in national inflation. Importantly, the growing FDI sector in Singapore has been found to contribute to the increase in the demand for tourism. In conclusion, the economic growth of a country could be identified as an important factor that should be a primary concern for tourism development. The findings of the study assists in developing policies and regulations to achieve sustainable tourism development in Sri Lanka.
Keywords: : Foreign Direct Investment; Gross Domestic Product; Inflation Rate; Macro economic Factors; Tourist Arrivals; Regional Tourism Competitors